The effect of changing the mode of ventilation on the arterial-to-end-tidal CO2 difference and physiological dead space in laterally and dorsally recumbent horses during halothane anesthesia - Teixeira Neto, Francisco José [UNESP]; Luna, Stélio Pacca Loureiro [UNESP]; Massone, Flavio; Thomassian, Armen; Vargas, José L. R.; Junior, José R. S.; D'Utra Vaz, Beatriz B.; Crocci, Adalberto José (Wiley, 2000)
Objective - To evaluate the effect of changing the mode of ventilation from spontaneous to controlled on the arterial-to-end-tidal CO2 difference [P(a-ET)CO2] and physiological dead space (VD(phys)/VT) in laterally and dorsally recumbent halothane-anesthetized horses. Study Design - Prospective, experimental, nonrandomized trial. Animals - Seven mixed breed adult horses (1 male and 6 female) weighing 320 ± 11 kg. Methods - Horses were anesthetized in 2 positions - right lateral and dorsal recumbency - with a minimum interval of 1 month. Anesthesia was maintained with halothane in oxygen for 180 minutes. Spontaneous ventilation (SV) was used for 90 minutes followed by 90 minutes of controlled ventilation (CV). The same ventilator settings were used for both laterally and dorsally recumbent horses. Arterial blood gas analysis was performed every 30 minutes during anesthesia. End-tidal CO2 (PETCO2) was measured continuously. P(a-ET)CO2 and VD(phys)/VT were calculated. Statistical analysis included analysis of variance for repeated measures over time, followed by Student-Newman-Keuls test. Comparison between groups was performed using a paired t test; P < .05 was considered significant. Results - P(a-ET)CO2 and VD(phys)/VT increased during SV, whereas CV reduced these variables. The variables did not change significantly throughout mechanical ventilation in either group. Dorsally recumbent horses showed greater P(a-ET)CO2 and VD(phys)/VT values throughout. PaCO2 was greater during CV in dorsally positioned horses. Conclusions and Clinical Relevance - Changing the mode of ventilation from spontaneous to controlled was effective in reducing P(a-ET)CO2 and physiological dead space in both laterally and dorsally recumbent halothane-anesthetized horses. Dorsal recumbency resulted in greater impairment of effective ventilation. Capnometry has a limited value for accurate estimation of PaCO, in anesthetized horses, although it may be used to evaluate pulmonary function when paired with arterial blood gas analysis. © Copyright 2000 by The American College of Veterinary Surgeons.
Keywords: halothane; inhalation anesthetic agent; animal; animal disease; artificial ventilation; body posture; female; horse; lung dead space; male; physiology; prospective study; Anesthetics, Inhalation; Animals; Female; Halothane; Horses; Male; Posture; Prospective Studies; Respiration, Artificial; Respiratory Dead Space